Revisión sobre aspectos farmacológicos a considerar para el uso de antibióticos en la camaronicultura - Varela-Mejías, Alexander (2018)
The incidence of infectious diseases in shrimp has increased the use of antibiotics as part of the response of producers, seeking to reduce losses caused by bacterial outbreaks. These treatments often lack knowledge concerning the pharmacological properties of the products. Data for these properties for oxytetracycline in shrimp are presented, being one of the most used antibiotics, in addition to data for other antibiotics.